Performance of Djallonké sheep fed untreated rice straw supplemented with urea-molasses block (UMB): II. Substitution of wheat flour in UMB with gari or kokonte flour - Egyir, I.K.; Amaning-Kwarteng, K.; Adjorlolo, L.K. (Ghana Society of Animal Production, 2010)
This study was designed to compare the effect of three sources of starch in urea molasses block fed to sheep. The urea molasses-block (UMB) contained either wheat flour (UMBW), or kokonte (dried cassava meal; UMBK) or gari (partially destarched cassava product; UMBG). All sheep were fed on a basal diet of untreated rice straw ad libitum and allowed to lick the urea-molasses blocks freely. Voluntary feed intake and weight gain, rumen pH and in sacco rumen degradation of the basal diet were measured using Djallonké sheep. Total dry matter and crude protein intakes were similar for UMBW and UMBK, both of which were lower (p<0.05) than for UMBG. Rumen pH decreased sharply for UMBW and UMBK but was more stable for UMBG. This was related to the changes in rumen degradation which showed greater improvement for the animals on UMBG than for those on UMBW and UMBK. It was concluded that UMBG was a better supplement than either UMBW or UMBK when sheep are fed rice straw. Gari which is a processed cassava meal with higher fibre content than dried cassava meal (kokonte) or wheat flour was the best source of starch in the formulation of urea-molasses blocks.
Keywords: Urea-molasses; wheat flour; gari; kokonte; supplementation; rice straw; sheep